1964
DOI: 10.1002/jsfa.2740151203
|View full text |Cite
|
Sign up to set email alerts
|

Some factors in low‐temperature storage influencing the mineralisable‐nitrogen of soils

Abstract: The effect of storing soils at −20° on their subsequent ability to mineralise nitrogen on incubation differs according to the soil, because significantly more mineral‐N (ammonium‐and nitrate‐N) and nitrate‐N was produced by three of four soils tested. These increases, apparently induced by freezing and thawing, may have been partly related to the moisture and carbon contents of the soils. Samples stored for different periods up to 6–9 months differed little in their rates of mineralisation. Experiments with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Results vary considerably among studies in the literature that examine effects of freezing on soil N. Harding and Ross (1964) found that thawing after freezing at -20 8C increased net N mineralization and nitrification in some, but not all, soils examined, concluding that moisture and C contents of soils may influence this response. The field-based snow manipulation study at Hubbard Brook Experimental Forest found that freezing (brought about by experimentally removing snowpack) resulted in increases in soil NO 3 and enhanced loss of N in soil solution, but did so without significantly influencing net nitrification Groffman et al 2001aGroffman et al , 2001b.…”
Section: Effects Of Freezing On Net N Mineralization and Net Nitrificmentioning
confidence: 90%
“…Results vary considerably among studies in the literature that examine effects of freezing on soil N. Harding and Ross (1964) found that thawing after freezing at -20 8C increased net N mineralization and nitrification in some, but not all, soils examined, concluding that moisture and C contents of soils may influence this response. The field-based snow manipulation study at Hubbard Brook Experimental Forest found that freezing (brought about by experimentally removing snowpack) resulted in increases in soil NO 3 and enhanced loss of N in soil solution, but did so without significantly influencing net nitrification Groffman et al 2001aGroffman et al , 2001b.…”
Section: Effects Of Freezing On Net N Mineralization and Net Nitrificmentioning
confidence: 90%
“…Water-holding capacities were determined on 50 g samples of soil (Harding and Ross 1964). pH was measured in a soil to water suspension of 1: 2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of water holding capacity was done by adapting the method used by Shinohara et al (1999) and followed by Harding and Ross (1964). By using filtered funnel with the lower part plugged with stopper, media samples were saturated in water at a ratio of 1 media: 2 water and left overnight.…”
Section: Water Holding Capacitymentioning
confidence: 99%